“Interdisciplinary” Legal Studies and the Emergence of New Academic Teachings: A Research Project on Law Courses in 19th-20th century Italy - Monti, Annamaria (CIAN-Revista de Historia de las Universidades, 2016)
The profound change in thinking about the law experienced by European jurists at the turning of the 20th century is well known: they renewed their methods, also through the influence of German legal thought and the impact of new social sciences. Focusing on the Italian experience, the research intends to investigate how this innovative change was linked to the teaching of law. Most certainly, new courses were introduced. Concerning the contents of the teachings, another point to investigate are the connections with the legal thought circulating at a transnational level in those times.
Keywords: legal education; legal doctrine; Italian universities (19th-20th centuries); teaching methods; legal studies